2021
DOI: 10.1016/j.amjmed.2021.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Stopping RAS Inhibitors in Advanced Chronic Kidney Disease and Cardiorenal Outcomes—Several Unanswered Questions Remain

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5] Nevertheless, there is substantial disagreement regarding the renal and cardiovascular outcomes after the discontinuation of RAAS blockade in patients with advanced CKD. [6][7][8] A recent Swedish Renal Registry study examined the impact of stopping versus continuing RAAS inhibitor therapy in 10,254 prevalent RAAS inhibitor users (median age 72 years, 36% female) with newonset eGFR <30 ml/min per 1.73 m2, 1553 (15%). 6 Median eGFR was 23 ml/min per 1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Nevertheless, there is substantial disagreement regarding the renal and cardiovascular outcomes after the discontinuation of RAAS blockade in patients with advanced CKD. [6][7][8] A recent Swedish Renal Registry study examined the impact of stopping versus continuing RAAS inhibitor therapy in 10,254 prevalent RAAS inhibitor users (median age 72 years, 36% female) with newonset eGFR <30 ml/min per 1.73 m2, 1553 (15%). 6 Median eGFR was 23 ml/min per 1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…7 We had in a recent editorial commentary in the American Journal of Medicine raised the concerns that such debate and controversy about cardiorenal outcomes following the discontinuation of RAAS blockade in advanced CKD remain unsettled. 8 Furthermore, we had earlier described the syndrome of late onset renal failure from angiotensin blockade (LORFFAB) and had demonstrated generally improved renal outcomes in patients presenting with progressive AKI after discontinuation of concurrent RAAS blockade without overt CV consequences. 9,10 The first author had therefore undertaken to complete a prospective study of similar patients with acutely presenting AKI on CKD following the elective withdrawal of concurrent RAAS blockade after moving to the University of Vermont, Burlington, VT in the US Northeast coast.…”
Section: Introductionmentioning
confidence: 99%
“…Unquestionably, there is a common consensus regarding cardiorenal protection with RAASB in both diabetic and nondiabetic CKD. Nevertheless, there remain conflicting retrospective reports regarding renal and cardiovascular mortality outcomes following discontinuation of RAASB in advanced CKD [2,3]. In a large Swedish Registry observational study of people with advanced CKD, stopping RAASB was associated with higher absolute risks of mortality and major adverse cardiovascular events, but with a lower risk of kidney replacement therapy [2].…”
Section: Editorialmentioning
confidence: 99%
“…We revisited the conflicting results of these studies in a commentary in the American Journal of Medicine. In this commentary, we reexamined the continuing debate and controversies surrounding renal and cardiovascular outcomes following the preemptive withdrawal of RAAS blockade in patients with advanced CKD [ 8 ]. Moreover, a Korean study, reported in 2017, investigated renal death, all-cause mortality, hospitalization for hyperkalemia, and interactive factors as composite outcomes in 2,076 pre-dialysis patients with advanced CKD on RAAS blockers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%